HUBUNGAN STATUS GIZI DENGAN KEJADIAN MENARCHE DINI PADA SISWI SEKOLAH DASAR DI KECAMATAN PATI, KABUPATEN PATI - Ayu Dya Puspaning Tyas; Lintang Dian Saraswati; Mateus Sakundarno Adi; Henry Setyawan Susanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Early menarche is the first menstruation in women in early adolescence that occurs under the age of 12 years. Nutritional status / BMI (Body Mass Index) can affect the occurrence of early menarche through the rate of growth and sexual maturity, which is an indicator of the occurrence of menarche. The aim of this study was to analyze the relationship of nutritional status with the incidence of early menarche in elementary school students. This type of study is analytical observational with cross-sectional study design. The sample of this study amounted to 110 elementary school students with early menarche and 110 elementary school students who experienced normal menarche. Data analysis was done by univariate and bivariate using the Spearman rank correlation test. The results of the analysis show that there is a relationship between nutritional status and early menarche incidence in elementary school students (p = 0.001, rs = -0.321). If children have more nutritional status, they will have an age of early menarche. It is hope that respondents who have excess nutritional status, control the consumption of foods containing fat.